2023
DOI: 10.1002/adma.202211155
|View full text |Cite
|
Sign up to set email alerts
|

Flattening Grain‐Boundary Grooves for Perovskite Solar Cells with High Optomechanical Reliability

Abstract: Optomechanical reliability has emerged as an important criterion for evaluating the performance and commercialization potential of perovskite solar cells (PSCs) due to the mechanical‐property mismatch of metal halide perovskites with other device layer. In this work, grain‐boundary grooves, a rarely discussed film microstructural characteristic, are found to impart significant effects on the optomechanical reliability of perovskite–substrate heterointerfaces and thus PSC performance. By pre‐burying iso‐butylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…1i. It is evident that when Nt = 10 16 cm -3 , the 2D/3D PSC exhibits nearly identical J-V behavior in contrast to the 3D PSC, but when Nt = 10 14 cm -3 , the 2D/3D PSC shows a much higher Voc, consistent with the experiment observations [16,17]. In the previous section, we confirmed that the 2D/3D structure can significantly improve the performance of PSCs in specially designed cases.…”
Section: Resultssupporting
confidence: 86%
“…1i. It is evident that when Nt = 10 16 cm -3 , the 2D/3D PSC exhibits nearly identical J-V behavior in contrast to the 3D PSC, but when Nt = 10 14 cm -3 , the 2D/3D PSC shows a much higher Voc, consistent with the experiment observations [16,17]. In the previous section, we confirmed that the 2D/3D structure can significantly improve the performance of PSCs in specially designed cases.…”
Section: Resultssupporting
confidence: 86%
“…As shown in Figure S12, both films showed perovskite characteristic peaks at ~14°and ~28°(corresponding to the 110 and 220 crystal planes, respectively). [16] The film with POF-HDDA exhibited a higher intensity, revealing the higher crystallinity and quality of the film treated by POF-HDDA. There were no additional diffrac-Angewandte Chemie tion peaks after the introduction of POF-HDDA, indicating that POF-HDDA did not enter the perovskite lattice.…”
Section: Methodsmentioning
confidence: 94%
“…We further investigated the quality of perovskite films with/without POF‐HDDA through X‐ray diffraction (XRD). As shown in Figure S12, both films showed perovskite characteristic peaks at ∼14° and ∼28° (corresponding to the 110 and 220 crystal planes, respectively) [16] . The film with POF‐HDDA exhibited a higher intensity, revealing the higher crystallinity and quality of the film treated by POF‐HDDA.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure S12, both films showed perovskite characteristic peaks at ~14°and ~28°(corresponding to the 110 and 220 crystal planes, respectively). [16] The film with POF-HDDA exhibited a higher intensity, revealing the higher crystallinity and quality of the film treated by POF-HDDA. There were no additional diffrac-Angewandte Chemie Forschungsartikel tion peaks after the introduction of POF-HDDA, indicating that POF-HDDA did not enter the perovskite lattice.…”
Section: Resultsmentioning
confidence: 94%